Senegal : Third and Fourth Reviews Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report, 2006)
This paper focuses on Senegal's Third and Fourth Reviews Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and Request for Waiver of Performance Criteria. Program implementation in 2005 was uneven. Most performance criteria (PCs) for the third and fourth reviews were met, except for the continuous PCs on the arrears of, and budgetary transfers to, the state electricity company, and the ceiling on no-bid public contracts. On the basis of the corrective actions taken and planned, the authorities requested waivers for the missed PCs.